Pulse injection metalorganic chemical vapour deposition of selected magnetic metal oxides - Zukova, Anna (Trinity College (Dublin, Ireland). School of Chemistry, 2009)
The main aim of this project is to prepare oxide based DMS and ferrimagnetic oxide layers for potential application in new generation spintronic devices. This work involves the preparation of Co-doped ZnO, Cr-doped ln2O3 and also ferrimagnetic Fe3O4 and CoFe2O4 thin films using PI MOCVD and investigation of their morphology, structure and magnetic properties. The new approach of growing thin films in external magnetic field is also developped in this work. It is anticipated that the external magnetic field can be used to tune the magnetic properties of the films during their growth and apply it for the preparation of spintronic devices.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.